Flexural behavior of representative panels of prefabricated reinforced masonry shells - Oliveira, Juliana T. (2004)
Reinforced masonry shells were widely used in the past by Eladio Dieste. In order to develop a modern competitive technology for the building industry, a prefabrication process to build such structures has been investigated and the necessary tests to characterize the constitutive materials have been carried out. Here, an experimental program of bending tests in reinforced masonry panels is detailed. The panels were made of a concrete topping layer reinforced with welded wire mesh, ceramic facing bricks and reinforced concrete joints. The panels were tested for both positive and negative bending moments. A numerical approach was developed to predict the deformational and the load bearing capacity of such structures.